2021
DOI: 10.11628/ksppe.2021.24.3.267
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Particulate Matter Removal Capacity of 11 Herbaceous Landscape Plants

Abstract: Background and objective Particulate matter (PM) has a fatal effect on health. There have been many studies on the use of plants such as trees and shrubs as eco-friendly and sustainable biofilter for the removal of PM. In forming more green space, ground cover plants play an important role in multi-layered planting. This study was conducted to investigate the ability of plants to reduce PM, targeting Korean native ground cover plants with high availability in urban green spaces. Methods For 4 species of Astera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Methods used to reduce fine dust include managing dust sources and managing indoor air quality using air conditioners or air purifiers. With the current state of global climate patterns and pollution, there has been increased interest in researching eco-friendly and sustainable methods to reduce PM, e.g., using plants [6][7][8]. Popek et al [9] found that the amount of fine dust adsorbed on the leaves of woody plants or accumulated into the wax layer was much higher on samples collected from plants near cities than that on leaves collected from the country side, where far less fine dust is produced.…”
Section: Introductionmentioning
confidence: 99%
“…Methods used to reduce fine dust include managing dust sources and managing indoor air quality using air conditioners or air purifiers. With the current state of global climate patterns and pollution, there has been increased interest in researching eco-friendly and sustainable methods to reduce PM, e.g., using plants [6][7][8]. Popek et al [9] found that the amount of fine dust adsorbed on the leaves of woody plants or accumulated into the wax layer was much higher on samples collected from plants near cities than that on leaves collected from the country side, where far less fine dust is produced.…”
Section: Introductionmentioning
confidence: 99%